Konsep Ecodesign Lanskap Jalan Arteri Kota Palangka Raya berbasis Kearifan Lokal Budaya Suku Dayak Ngaju - Roma Librawan; Andi Gunawan; Waju Qamara Mugnisjah (TATALOKA, 2021)
Streetscape RTA Milono in Palangka Raya city is a part of green open space which has the potential improved the ecological, aesthetic, and preservation of local wisdom in strengthening the character of landscape as a city identity. The study aimed to identify the local wisdom potential of Dayak Ngaju culture, then to analysed the basis of a design concept that met ecological design principles; and arrange it as a recommendation for streetscape ecodesign concept. The ecodesign concept is based on applied local wisdom as an alternative solution to streetscape problems. This study used descriptive qualitative method. Local wisdom can be form into tangible and intangible. The results of the study found the potential of the local wisdom of the Dayak Ngaju culture as a basis for the design concept and fulfilled the principles of ecological design, there are: Huma Betang and the landscape, Tabat, Beje, Handil, Pamatang, Tajahan, Kaleka, Sepan, Pukung pahewan, Balanga, Kalang, Telawang, Lawang sakepeng, philosophy of Batang garing, Belom bahadat, philosophy of river, and orientation value; basic concept of “Eco-Cultural-Streetscape Restoration”, which is to restored the character of the streetscape, ecological functions with the local wisdom of the Dayak Ngaju culture.